The petroleum industry in the United Kingdom: proceedings of the joint meeting of the institute of petroleum and the Deutsche Gesellschaft fur Mineralolwissenschaft und Kohlechemie - Institute of Petroleum (Great Britain). Process Analysers Panel; Hepple, Peter (London, 1966)
36